Impact of domestication in the production of the class II lanthipeptide lichenicidin by bacillus licheniformis I89 - Caetano, Tânia
Investigation on lantibiotics biosynthesis constitutes an emergent field, since these molecules have demonstrated a great potential to replace the so-called ‘‘traditional antibiotics’’. The adaptation of bacteria to laboratory conditions (domestication) is an unpredictable phenomenon, which sometimes is associated with the loss of important biotechnological properties. In this study, the domestication of Bacillus licheniformis was associated with the production of the lantibiotic lichenicidin, a twopeptide lantibiotic with activity against several Grampositive bacteria.